2004
DOI: 10.1177/00343552030470020401
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Employment Status for People with Multiple Sclerosis

Abstract: This study examined the relevance of the disease-and-demographics model for explaining the employment outcomes of adults with multiple sclerosis (MS). Participating in a national survey of their employment concerns, 1,310 adults with MS provided data for the study (274 men, 21%; 1,020 women, 78%; 16 participants did not identify their gender). With an average age of 50 ( SD = 12.14), most of the respondents were White (92%), well educated (97% were high school graduates, 40% were college graduates), and residi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
56
2
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(59 citation statements)
references
References 15 publications
0
56
2
1
Order By: Relevance
“…Patients become limited not only in employment but also educational opportunities, or interpersonal relationships as well [3][4][5]. Functional disability has been associated with restricted social participation.…”
Section: Introductionmentioning
confidence: 99%
“…Patients become limited not only in employment but also educational opportunities, or interpersonal relationships as well [3][4][5]. Functional disability has been associated with restricted social participation.…”
Section: Introductionmentioning
confidence: 99%
“…Both men and women with MS are more likely to leave the work force if they have a spouse who is working [18]. People with MS who have higher levels of education and/or more money in savings and investments are more likely to be employed than are those in lower socioeconomic strata [10,19]. This finding may not be surprising given that people with higher levels of education tend to occupy positions that require less physical exertion, and the physiological effects of MS therefore may not impose work impediments to the extent that they do for those whose jobs require more physical exertion.…”
Section: Demographic Factorsmentioning
confidence: 99%
“…Roessler et al [19] found that people who experience MS symptoms most or all of the time, especially if the persistent symptoms are greater in number and more severe, are more likely to be unemployed than people with other symptom patterns. More symptoms, more persistent symptoms, and more severe symptoms are generally associated with primary or secondary progressive MS, so it follows that people with progressive forms of the disease are at greater risk for job loss than people whose MS experience is more episodic and/or less intrusive.…”
Section: Disease-related Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…5 In previous research, factors related to unemployment have been found to include level of disability (generally measured by the Expanded Disability Status Scale [EDSS]), 1,6,7 age, 1,2,8,9 cognitive functioning, [8][9][10] education level, 7,9,11,12 disease subtype, 2,13 disease duration, 2,8 and gender. 1 In one of the larger studies (N = 1310) on employment and MS, Roessler et al 14 evaluated the relationship of persistence of symptoms, severity of symptoms, educational attainment, affective symp-toms (yes/no), and cognitive symptoms (yes/no) with the categorical outcome variable, employed/not employed, and found that persistence and severity of symptoms, education, and presence of cognitive symptoms were related to employment status. In general, however, study findings have been inconsistent, with little examination of the role of multiple secondary health factors and conditions on employment.…”
mentioning
confidence: 99%